Learning Mandarin the fun way using Smart Partnership Programme - Chong, Ah Kow
Thirty Universiti Malaysia Pahang (UMP) undergraduates and 30 pupils from Sekolah Jenis Kebangsaan Cina (SJKC) Gambang took part in a fun-filled one-day programme organised by the Mandarin Language and Culture Centre (MLCC) and Foreign Languages Department of Centre for Modern Languages & Human Sciences (CMLHS).